Positive electrode active material for lithium secondary battery, positive electrode for lithium secondary battery comprising same, and lithium secondary battery

CN122930899APending Publication Date: 2026-10-16SK ON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610456461.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-04-03
Filing Date
2026-04-08
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

根据本发明的示例性的实施方案的正极活性物质通过将圆度的平均值和圆度的相对标准偏差调节为规定范围,可以减少正极压制(press)时发生的正极活性物质颗粒的破碎。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930899A_ABST
    Figure CN122930899A_ABST
Patent Text Reader

Abstract

A positive electrode active material for a lithium secondary battery according to an exemplary embodiment of the present application includes: large particles; and small particles having an average particle diameter (D 50 ) smaller than the large particles. The average of the roundness of the large particles is 0.95 or more and less than 1. The ratio (C S / C L ) of the average of the roundness of the small particles (C S ) to the average of the roundness of the large particles (C L ) is 0.90 to 0.99. The relative standard deviation of the roundness of the large particles is 1 to 5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a positive electrode active material for lithium secondary batteries, a positive electrode for lithium secondary batteries containing the same, and a lithium secondary battery. Background Technology

[0002] Rechargeable batteries are batteries that can be recharged and discharged repeatedly. With the development of the information communication and display industries, rechargeable batteries are widely used as power sources for portable electronic communication devices such as portable cameras, mobile phones, and laptops. In addition, in recent years, battery packs including rechargeable batteries have been developed and applied as power sources for environmentally friendly vehicles such as electric vehicles.

[0003] Secondary batteries can be categorized into, for example, lithium secondary batteries, nickel-cadmium batteries, and nickel-metal hydride batteries. Among them, lithium secondary batteries have high operating voltage and energy density per unit weight, and are advantageous for charging speed and lightweight design, so they are actively being researched and developed.

[0004] For example, NCM-based active materials containing nickel, cobalt, and manganese are being used as positive electrode active materials in lithium-ion batteries. Furthermore, as the application of lithium-ion batteries expands to large devices such as electric vehicles, there is a need to develop positive electrodes with high electrode density to ensure the high capacity of lithium-ion batteries.

[0005] During the fabrication of the positive electrode, pressure is applied to further increase its density, which may cause the active material particles to break down. In this case, the electrochemical characteristics and long-term lifespan of the lithium-ion battery may be reduced.

[0006] Therefore, it is necessary to design positive electrode active material particles to prevent breakage of positive electrode active material particles during the fabrication of the positive electrode. Summary of the Invention

[0007] (a) Technical problems to be solved One technical problem of the present invention is to provide a positive electrode active material for lithium secondary batteries with improved electrochemical properties and improved lifespan properties.

[0008] One technical problem of the present invention is to provide a positive electrode for a lithium secondary battery and a lithium secondary battery comprising the positive electrode active material.

[0009] (II) Technical Solution According to an exemplary embodiment of the present invention, a positive electrode active material for a lithium secondary battery comprises: large particles and small particles, wherein the average particle size (D) of the small particles is... 50 The particles are smaller than the larger particles. The average circularity of the large particles is greater than 0.95 and less than 1, while the average circularity of the small particles is smaller than that of the larger particles. S) and the average roundness of the large particles (C L The ratio of (C) S / C L The relative standard deviation of the roundness of the large particles is 0.90 to 0.99, and the roundness is defined by Equation 1 below.

[0010] [Formula 1] Roundness = 4π × (A / P) 2 ) In Equation 1, A is the area of ​​the particle cross-section, and P is the perimeter of the particle cross-section.

[0011] In an exemplary embodiment, the large particles and the small particles may comprise lithium nickel metal oxide particles.

[0012] In an exemplary embodiment, the lithium nickel metal oxide particles may be represented by the following chemical formula 1.

[0013] [Chemical Formula 1] Li x Ni a M b O 2+z In the chemical formula 1, M is at least one element selected from B, Al, Si, Ti, V, Cr, Mg, Mn, Fe, Co, Cu, Zn, Y, Nb, Zr, Mo, Sn, Sr and W, with 0.9≤x≤1.2, 0.6≤a≤0.99, 0.01≤b≤0.4, and -0.5≤z≤0.1.

[0014] In an exemplary embodiment, in chemical formula 1, the value can be 0.8 ≤ a ≤ 0.95.

[0015] In an exemplary embodiment, the average particle size (D) of the large particles 50 The size can be greater than 10.0 μm and less than 15.0 μm.

[0016] In an exemplary embodiment, the average particle size (D) of the small particles 50 The size can be greater than 1.0 μm and less than 8.0 μm.

[0017] In an exemplary embodiment, the average roundness (C) of the large particles L The value can be greater than 0.97 and less than 1.

[0018] In an exemplary embodiment, the average roundness (C) of the large particles L The value can be greater than 0.99 and less than 1.

[0019] In an exemplary embodiment, the average (C) of the roundness of the small particles S ) and the average roundness of the large particles (C L The ratio of (C) S / C L The value can be between 0.92 and 0.97.

[0020] In an exemplary embodiment, the average (C) of the roundness of the small particles S ) and the average roundness of the large particles (C L The ratio of (C) S / C L The value can be between 0.93 and 0.96.

[0021] In an exemplary embodiment, the relative standard deviation of the roundness of the large particles can be from 1 to 4.

[0022] In an exemplary embodiment, the relative standard deviation of the roundness of the large particles can be between 1 and 3.

[0023] In an exemplary embodiment, the mixing weight ratio of the large particles to the small particles can be from 6:4 to 9:1.

[0024] A positive electrode for a lithium secondary battery according to an exemplary embodiment of the present invention includes: a positive electrode current collector; and a positive electrode active material layer, the positive electrode active material layer comprising the aforementioned positive electrode active material for a lithium secondary battery formed on the positive electrode current collector.

[0025] A lithium secondary battery according to an exemplary embodiment of the present invention includes: a positive electrode comprising the above-described positive electrode active material for lithium secondary batteries; a negative electrode disposed opposite to the positive electrode; and a separator disposed between the positive electrode and the negative electrode.

[0026] (III) Beneficial Effects According to an exemplary embodiment of the present invention, the positive electrode active material can reduce the breakage of positive electrode active material particles during positive electrode pressing by adjusting the average value of roundness and the relative standard deviation of roundness to a specified range.

[0027] According to an exemplary embodiment, by adjusting the sphericity ratio of the small to large particles of the positive electrode active material to a specified range, the long-term life characteristics of the lithium secondary battery can be improved.

[0028] The lithium secondary battery according to the exemplary implementation can be widely used in green technology fields such as electric vehicles, battery charging stations, solar power generation using batteries, and wind power generation. For example, the lithium secondary battery can be used in eco-friendly electric vehicles and hybrid vehicles to prevent climate change by suppressing air pollution and greenhouse gas emissions. Attached Figure Description

[0029] Figure 1 and Figure 2 These are schematic plan views and schematic cross-sectional views of a lithium secondary battery according to an exemplary embodiment.

[0030] Explanation of reference numerals in the attached figures 100: Positive electrode; 105: Positive electrode current collector 107: Positive electrode lead; 110: Positive electrode active material layer 120: Negative electrode active material layer; 125: Negative electrode current collector 127: Negative lead; 130: Negative electrode 140: Diaphragm; 150: Electrode assembly 160: Casing Detailed Implementation

[0031] According to an exemplary embodiment of the present invention, a positive electrode active material is provided that adjusts the average value of roundness and the relative standard deviation of roundness to a predetermined range. Furthermore, a lithium secondary battery comprising the positive electrode active material and having improved lifespan characteristics is provided.

[0032] Exemplary embodiments will be described in more detail with reference to the accompanying drawings. However, the drawings and embodiments appended to this specification are only for further understanding of the technical concept of the invention, and therefore the invention should not be limited to the content described in such drawings and embodiments.

[0033] The term "small particles" as used in this invention may refer to the average particle size (D). 50 Positive electrode active material with a size greater than 1.0 μm and less than 8.0 μm.

[0034] The term "large particles" as used in this invention may refer to the average particle size (D). 50 Positive electrode active material with a size greater than 10.0 μm and less than 15.0 μm.

[0035] The term "average particle size (D)" used in this invention 50"Particle size distribution" can refer to the longest diameter of particles at the 50% volume fraction in the cumulative particle size distribution. The particle size of the positive electrode active material can be measured using scanning electron microscopy (SEM), transmission electron microscopy (TEM), light scattering, or laser diffraction. For example, the particle size distribution of the positive electrode active material can be measured by dispersing the positive electrode active material in a dispersion medium and then using a laser diffraction particle size analyzer.

[0036] The positive electrode active material according to the exemplary embodiment may comprise large particles and small particles.

[0037] According to the exemplary embodiment, the positive electrode active material, by comprising large and small particles of different sizes, can pack more particles within a given space. For example, small particles can be uniformly dispersed and distributed among the large particles. In this case, damage to the positive electrode active material particles due to excessive pressure or compression can be prevented, and a high packing density can be achieved. Therefore, the energy density per unit volume of the electrode can be increased.

[0038] According to the exemplary embodiment, the average roundness of the large particles (C) L The value can be greater than 0.95 and less than 1.

[0039] According to the exemplary embodiment, the average roundness of the large particles (C) L The value can be 0.96 or higher, 0.97 or higher, 0.98 or higher, or 0.99 or higher. According to the exemplary embodiment, the average (C) of the roundness of the large particles... L () can be less than 1.

[0040] Within the aforementioned range, the overall sphericity of the positive electrode active material for lithium secondary batteries can be high, which can improve structural stability. For example, when the average sphericity of large particles (C...) L When the average sphericity (C) of large particles is less than 0.95, the particle strength decreases, potentially leading to particle breakage or damage during high-voltage operation and charge / discharge processes. For example, when the average sphericity of large particles (C) is less than 0.95, the particle strength decreases, potentially leading to particle breakage or damage during high-voltage operation and charge / discharge processes. L When the value is 1, although the positive electrode active material has a high degree of stacking, the production time for particles that meet this roundness requirement increases, which may reduce production efficiency, such as a decrease in yield.

[0041] The average roundness of the large particles (C) LThe value could be the average calculated after measuring the roundness of the large particles. For example, it could be the average calculated after measuring the roundness of the corresponding large particles among 10,000 positive electrode active material particles using a Morphologi device.

[0042] For example, the large particles can be spherical. A complete sphere has a roundness value of 1, and the closer the roundness value of a particle is to 1, the closer the shape of the particle is to a complete sphere.

[0043] In an exemplary embodiment, the roundness of the particle can be calculated by the square of the ratio of the circumference of a circle having the same area as the particle to the circumference of the particle. For example, the roundness of the particle can be calculated using Equation 1 below.

[0044] [Formula 1] Roundness = 4π × (A / P) 2 ) In Equation 1, A can be the area of ​​the particle cross-section, and P can be the perimeter of the particle cross-section.

[0045] The area and perimeter of the particle cross-section can be observed using an optical microscope, and measured from the obtained images using image analysis software such as ImageJ. Alternatively, the sphericity of the particles can be measured using a particle morphology analysis device (flow particle image analyzer), such as the Malvern Morphologi 4.

[0046] In an exemplary embodiment, the average sphericity (C0) of the small particles in the positive electrode active material is... S The sphericity can be smaller than the average (C) of large particles. L ).

[0047] With the average roundness of large particles (C) L The average roundness of the smaller particles (C) is greater than that of the smaller particles. S The increased contact area between the positive electrode active materials and the shorter electron conduction path improve the conductivity of the positive electrode. Furthermore, the easier diffusion of lithium ions leads to faster charge and discharge rates, thereby increasing the power output of the secondary battery.

[0048] The average roundness of the small particles (C) S The value could be the average calculated after measuring the roundness of the small particles. For example, it could be the average calculated after measuring the roundness of the corresponding small particles among 10,000 positive electrode active material particles using a Morphologi device.

[0049] For example, the small particles can be spherical.

[0050] For example, the average roundness of small particles (C S It can be greater than 0.855 and less than 0.99.

[0051] In an exemplary embodiment, the average roundness of the small particles (C) S ) and the average roundness of large particles (C L The ratio of (C) S / C L The values ​​can be 0.90 to 0.99, 0.91 to 0.98, 0.92 to 0.97, or 0.93 to 0.96.

[0052] For example, when the average roundness of small particles (C) S ) and the average roundness of large particles (C L The ratio of (C) S / C L When the average sphericity of the small particles is less than 0.90, the stress intensity between the particles increases due to the relatively smaller sphericity. Therefore, the secondary battery may experience particle breakage or damage during high-voltage operation or charging and discharging. For example, when the average sphericity of the small particles (C) is less than 0.90, the stress intensity between the particles increases. S ) and the average roundness of large particles (C L The ratio of (C) S / C L When the sphericity exceeds 0.99, although the sphericity of large and small particles is similar, the sphericity of large particles becomes relatively smaller. Therefore, the surface stress increases when large particles come into contact, which may lead to particle breakage and damage. Within the above range, it is possible to improve the conductivity, ion diffusion, and energy density of the positive electrode while preventing the breakage of the positive electrode active material particles.

[0053] In an exemplary embodiment, the relative standard deviation (%RSD) of the roundness of the large particles is 1 to 5, 1 to 4, 1 to 3, or 1 to 2.

[0054] The relative standard deviation is the value calculated by dividing the standard deviation of roundness by the average roundness and then multiplying by 100.

[0055] Within the aforementioned range, the overall energy density of lithium-ion batteries can be improved, as well as their thermal stability and lifespan characteristics. For example, when the relative standard deviation of large particles is less than 1, although the uniformity of particle morphology is very high, it may reduce the production efficiency of large particles that meet this range.

[0056] For example, when the relative standard deviation of large particles exceeds 5, the uniformity of particle morphology decreases, which may lead to poor long-term performance at room temperature and high temperature, and reduced charge and discharge efficiency and discharge capacity, which may reduce energy density.

[0057] In an exemplary embodiment, the mixing weight ratio of large particles to small particles can be 6:4 to 9:1, 7:3 to 85:15, or 75:25 to 8:2. Within these ranges, the secondary battery can achieve high energy density while improving thermal stability and conductivity.

[0058] According to the exemplary embodiment, the average particle size (D) of the large particles 50 The size can be greater than 10.0 μm and less than 15.0 μm. For example, it can be from 10.5 μm to 14.0 μm or from 11 μm to 13.5 μm.

[0059] The average particle size (D) of the small particles according to the exemplary embodiment 50 The micrometer can be greater than 1.0 μm and less than 8.0 μm. For example, it can be 2.0 μm to 6.5 μm, 3.0 μm to 5.0 μm, or 3.5 μm to 4.5 μm.

[0060] The positive electrode active material according to an exemplary embodiment may contain a material capable of reversibly intercalating and deintercalating lithium ions.

[0061] According to an exemplary embodiment, the positive electrode active material may comprise lithium nickel metal oxide particles. The lithium nickel metal oxide particles may further comprise at least one of cobalt (Co), manganese (Mn), and aluminum (Al).

[0062] In some embodiments, the positive electrode active material or the lithium nickel metal oxide particles may include a layered structure or a crystal structure represented by the following chemical formula 1.

[0063] [Chemical Formula 1] Li x Ni a M b O 2+z In the chemical formula 1, the values ​​can be 0.9≤x≤1.2, 0.6≤a≤0.99, 0.01≤b≤0.4, and -0.5≤z≤0.1. In one embodiment, the values ​​in chemical formula 1 can be 0.8≤a≤0.95.

[0064] In the chemical formula 1, M can be at least one element selected from B, Al, Si, Ti, V, Cr, Mg, Mn, Fe, Co, Cu, Zn, Y, Nb, Zr, Mo, Sn, Sr, and W. For example, in the chemical formula 1, M can be at least one element selected from B, Al, Si, Ti, Cr, Mg, Y, Nb, Zr, Mo, Sr, and W.

[0065] The chemical structure represented by Formula 1 indicates the bonding relationships contained in the layered or crystalline structure of the positive electrode active material, and does not exclude other additional elements. For example, M may contain Co and / or Mn, and Co and / or Mn may be provided together with Ni as the main active element of the positive electrode active material. Formula 1 is provided to represent the bonding relationships of the main active elements and should be understood as including the introduction and substitution of additional elements.

[0066] In one embodiment, in addition to the primary active element, auxiliary elements may be further included to enhance the chemical stability of the positive electrode active material or the layered / crystal structure. These auxiliary elements may be incorporated into the layered / crystal structure and form bonds; this should be understood to also include the chemical structures represented by Formula 1.

[0067] The auxiliary element may include at least one of, for example, Na, Mg, Ca, Y, Ti, Hf, V, Nb, Ta, Cr, Mo, W, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Sn, Sr, Ba, Ra, P, or Zr. The auxiliary element may function as an auxiliary active element, together with Co or Mn, to contribute to the capacity / power activity of the positive electrode active material; for example, Al.

[0068] For example, the positive electrode active material or the lithium metal oxide may include a layered structure or a crystal structure represented by the following chemical formula 1-1.

[0069] [Chemical Formula 1-1] Li x Ni a M1 b1 M2 b2 O 2+z In the aforementioned chemical formula 1-1, M1 can be at least one element selected from B, Al, Si, Ti, V, Cr, Mn, Fe, Co, Cu, Zn, Y, Zr, Mo, Sn, Sr, and W. M2 can contain the aforementioned auxiliary elements and can be 0.9≤x≤1.2, 0.6≤a≤0.99, 0.01≤b1+b2≤0.4, and -0.5≤z≤0.1.

[0070] The positive electrode active material may further include coating elements or doping elements. For example, elements that are substantially the same as or similar to the auxiliary elements described above can be used as coating elements or doping elements. For example, one or more combinations of the elements described above can be used as coating elements or doping elements.

[0071] The coating element or doping element may exist on the surface of the lithium-nickel metal oxide particles, or may penetrate through the surface of the lithium-nickel metal oxide particles and be contained in the bonding structure represented by chemical formula 1 or chemical formula 1-1.

[0072] The positive electrode active material may contain nickel-cobalt-manganese (NCM)-based lithium oxide. In this case, NCM-based lithium oxide with increased nickel content can be used.

[0073] Ni can be provided as a transition metal related to the power and capacity of lithium secondary batteries. Therefore, as described above, by using a high-content (high-Ni) composition in the positive electrode active material, a high-capacity positive electrode and a high-capacity lithium secondary battery can be provided.

[0074] However, with increasing Ni content, the long-term storage stability and lifetime stability of the cathode or lithium secondary battery may relatively decrease, and side reactions with the electrolyte may also increase. However, according to an exemplary embodiment, conductivity can be maintained by including Co, while lifetime stability and capacity retention characteristics can be improved by including Mn.

[0075] The Ni content in the NCM-based lithium oxide (e.g., the mole fraction of nickel in the total moles of nickel, cobalt, and manganese) can be 0.6 or more, 0.7 or more, or 0.8 or more. In some embodiments, the Ni content can be 0.8 to 0.95, 0.82 to 0.95, 0.83 to 0.95, 0.84 to 0.95, 0.85 to 0.95, or 0.88 to 0.95.

[0076] In some embodiments, the positive electrode active material may further comprise lithium cobalt oxide-based active material, lithium manganese oxide-based active material, lithium nickel oxide-based active material, or lithium iron phosphate (LFP)-based active material (e.g., LiFePO4).

[0077] In some embodiments, the positive electrode active material may include, for example, a Mn-rich based active material having a chemical structure or crystal structure represented by Chemical Formula 2, a Li rich layered oxide (LLO) / Over Lithiated Oxide (OLO) based active material, or a Co-less based active material.

[0078] [Chemical Formula 2] p[Li2MnO3]·(1-p)[Li q JO2] In Chemical Formula 2, 0<p<1, 0.9≤q≤1.2, and J may include at least one element selected from Mn, Ni, Co, Fe, Cr, V, Cu, Zn, Ti, Al, Mg and B.

[0079] Hereinafter, a method for preparing the positive electrode active material according to the above embodiments of the present invention is provided.

[0080] According to an exemplary embodiment, an active material metal source may be prepared. The active material metal source includes a nickel source, and may further include a manganese source and / or a cobalt source.

[0081] Examples of the nickel source may include nickel sulfate (NiSO4), nickel hydroxide (Ni(OH)2), nickel nitrate (Ni(NO3)2), nickel acetate (Ni(CH3CO2)2), hydrates thereof, and the like. Examples of the manganese source may include manganese sulfate (MnSO4), manganese hydroxide (Mn(OH)2), manganese nitrate (Mn(NO3)2), manganese acetate (Mn(CH3CO2)2), hydrates thereof, and the like. Examples of the cobalt source may include cobalt sulfate (CoSO4), cobalt hydroxide (Co(OH)2), cobalt nitrate (Co(NO3)2), cobalt carbonate (CoCO3), hydrates thereof, and the like.

[0082] In one embodiment, nickel sulfate, manganese sulfate and cobalt sulfate may be used as the nickel source, manganese source and cobalt source respectively.

[0083] According to an exemplary embodiment, the above active material sources are mixed and reacted, for example, through a co-precipitation method, so that an active material precursor can be obtained. For example, the active material precursor may be prepared in the form of nickel-manganese hydroxide or nickel-manganese-cobalt hydroxide.

[0084] To promote the above co-precipitation reaction, a precipitant and / or a chelating agent may be used. The precipitant may include an alkaline compound such as sodium hydroxide (NaOH), sodium carbonate (Na2CO3) and the like. The chelating agent may include, for example, ammonia water, ammonium carbonate and the like.

[0085] The active material precursor can be mixed with the aforementioned auxiliary element source and lithium source, and then reacted through heat treatment to prepare lithium transition metal oxide particles. For example, the heat treatment temperature can be approximately 600°C to 850°C.

[0086] The lithium source may include, for example, lithium carbonate (Li₂CO₃), lithium nitrate (LiNO₃), lithium acetate (CH₃COOLi), lithium oxide (Li₂O), lithium hydroxide (LiOH), etc. These can be used alone or in combination of two or more. In one embodiment, the lithium source may be lithium hydroxide.

[0087] The source of the auxiliary element may comprise a compound containing at least one of B, Al, Y, Fe, and Cr. For example, oxides or hydroxides of at least one of B, Al, Y, Fe, and Cr can be used as the source of the aforementioned auxiliary element. Boric acid can also be used as a boron source.

[0088] According to some implementation schemes, the surface of the lithium transition metal oxide particles may contain impurities such as LiOH and Li2CO3. These impurities can be removed by washing with water-based solvents or organic solvents.

[0089] The following provides a lithium secondary battery comprising a positive electrode active material according to the above-described embodiment of the present invention.

[0090] Figure 1 and Figure 2 These are schematic plan views and schematic cross-sectional views illustrating a lithium secondary battery according to an exemplary embodiment. For example, Figure 2 It is along Figure 1 A cross-sectional view taken along the thickness direction of the I-I' line.

[0091] Reference Figure 1 and Figure 2 The lithium secondary battery may include an electrode assembly comprising a positive electrode 100, a negative electrode 130, and a separator 140 disposed between the positive and negative electrodes. The electrode assembly may be contained in a housing 160 and immersed in the electrolyte.

[0092] The positive electrode 100 may include a positive electrode active material layer 110, which is formed by coating the positive electrode active material onto the positive electrode current collector 105.

[0093] For example, the positive current collector 105 may include stainless steel, nickel, aluminum, titanium, or alloys thereof. The positive current collector may also include aluminum or stainless steel surface-treated with carbon, nickel, titanium, or silver. For example, the thickness of the positive current collector 105 may be from 10 μm to 50 μm.

[0094] For example, the positive electrode active material can be mixed in a solvent to prepare a positive electrode slurry. The positive electrode slurry can be coated onto the positive electrode current collector 105 and then dried and calendered to prepare the positive electrode active material layer 110. The coating process may include gravure coating, slot die coating, multilayer simultaneous die coating, embossing, doctor blade coating, dip coating, bar coating, casting, etc. The positive electrode slurry may further contain a binder and a conductive material.

[0095] Non-limiting examples of solvents used in the preparation of the positive electrode slurry include N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, N,N-dimethylaminopropylamine, ethylene oxide, tetrahydrofuran, etc.

[0096] The adhesive may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-co-hexafluoropropylene copolymer (poly(vinylidene fluoride-co-hexafluoropropylene)), polyacrylonitrile, polymethyl methacrylate, nitrile rubber (NBR), polybutadiene rubber (BR), styrene-butadiene rubber (SBR), polyacrylic acid-based adhesives, and poly(3,4-ethylenedioxythiophene) (PEDOT)-based adhesives, etc. In some embodiments, a PVDF-based adhesive may be used as the positive electrode adhesive.

[0097] The conductive material can be added to enhance conductivity and / or the mobility of lithium ions or electrons. For example, non-limiting examples of the conductive material may include carbon-based conductive materials such as graphite, carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, vapor-grown carbon fiber (VGCF), and carbon fibers, and / or metal-based conductive materials including perovskite materials such as tin, tin oxide, titanium oxide, LaSrCoO3, and LaSrMnO3.

[0098] The negative electrode 130 may include a negative electrode current collector 125 and a negative electrode active material layer 120, wherein the negative electrode active material layer 120 contains negative electrode active material and is formed on at least one side of the negative electrode current collector 125.

[0099] Non-limiting examples of the negative electrode current collector 125 may include copper foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper, polymer substrates coated with a conductive metal, and the like. The thickness of the negative electrode current collector 125 may be, for example, 10 μm to 50 μm.

[0100] The negative electrode active material may be a well-known substance in the art that allows lithium ions to intercalate and deintercalate without particular limitation. For example, the negative electrode active material may use carbon-based materials such as crystalline carbon, amorphous carbon, carbon composites, and carbon fibers, lithium metal, lithium alloys, silicon-containing substances, tin-containing substances, and the like.

[0101] Examples of the amorphous carbon may include hard carbon, soft carbon, coke, mesocarbon microbead (MCMB), mesophase pitch-based carbon fiber (MPCF), and the like.

[0102] Examples of the crystalline carbon may include graphite-based carbon such as natural graphite, artificial graphite, graphitized coke, graphitized MCMB, and graphitized MPCF.

[0103] The lithium metal may include pure lithium metal or lithium metal formed with a protective layer for suppressing dendrite growth and the like. In one embodiment, a lithium metal-containing layer deposited or coated on the negative electrode current collector may be used as the negative electrode active material layer. In one embodiment, a lithium thin film layer may be used as the negative electrode active material layer.

[0104] Examples of elements contained in the lithium alloy may include aluminum, zinc, bismuth, cadmium, antimony, silicon, lead, tin, gallium, indium, and the like.

[0105] The silicon-containing substance may provide further enhanced capacity characteristics. The silicon-containing substance may include Si, SiO x (0<x<2), metal-doped SiO x (0<x<2), silicon-carbon composites, and the like. The metal may include lithium and / or magnesium, and the metal-doped SiO x (0<x<2) may include metal silicate.

[0106] In some embodiments, the negative electrode active material may be mixed and stirred with a binder, a conductive material and / or a dispersing material in a solvent to prepare a negative electrode slurry. The negative electrode slurry may be coated on at least one side of the negative electrode current collector, followed by drying and rolling to fabricate the negative electrode 130.

[0107] As the adhesive and conductive material, substances of substantially the same or similar kind as those contained in the positive electrode can be used. In some embodiments, the negative electrode adhesive can be a styrene-butadiene rubber (SBR) based adhesive, carboxymethyl cellulose (CMC), polyacrylic acid based adhesive, poly(3,4-ethylenedioxythiophene), PEDOT based adhesive, etc.

[0108] The diaphragm 140 may comprise a porous polymer membrane or a porous nonwoven fabric. The porous polymer membrane may comprise polyolefin-based polymers such as ethylene polymers, propylene polymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers. The porous nonwoven fabric may comprise high-melting-point glass fibers, polyethylene terephthalate fibers, etc. The diaphragm 140 may also comprise a ceramic-based material. For example, inorganic particles may be coated on or dispersed within the polymer membrane to improve heat resistance.

[0109] According to an exemplary embodiment, the battery cell can be defined by a positive electrode 100, a negative electrode 130, and a separator 140, and can be formed, for example, by stacking multiple battery cells. The electrode assembly 150 can be of the winding type, stacking type, z-folding type, or stack-folding type.

[0110] The electrode assembly 150 can be housed together with the electrolyte in the housing 160, thereby defining a lithium secondary battery. According to an exemplary embodiment, the electrolyte can be a non-aqueous electrolyte.

[0111] The non-aqueous electrolyte comprises a lithium salt as the electrolyte and an organic solvent, wherein the lithium salt is, for example, Li... + X - This indicates that the anion (X) of the lithium salt is... - ), can be exemplified by F - Cl - ,Br - I - NO3 - N(CN)2 - BF4 - ClO4 - PF6 - (CF3)2PF4 - (CF3)3PF3- (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - CF3CF2SO3 - (CF3SO2)2N - (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - (CF3CF2SO2)2N - wait.

[0112] The organic solvents may include, for example, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, γ-butyrolactone, propylene sulfite, tetrahydrofuran, etc. These may be used alone or in combination of two or more.

[0113] In some implementations, a solid electrolyte can be used instead of the non-aqueous electrolyte described above. In this case, the lithium secondary battery can be manufactured as an all-solid-state battery. Furthermore, a solid electrolyte layer can be disposed between the positive and negative electrodes instead of the aforementioned separator.

[0114] The solid electrolyte may include a sulfide-based electrolyte. As a non-limiting example, the sulfide-based electrolyte may include Li₂S-P₂S₅, Li₂S-P₂S₅-LiCl, Li₂S-P₂S₅-LiBr, Li₂S-P₂S₅-LiCl-LiBr, Li₂S-P₂S₅-Li₂O, Li₂S-P₂S₅-Li₂O-LiI, Li₂S-SiS₂, Li₂S-SiS₂-LiI, Li₂S-SiS₂-LiBr, Li₂S-SiS₂-LiCl, Li₂S-SiS₂-B₂S₃-LiI, Li₂S-SiS₂-P₂S₅-LiI, Li₂S-B₂S₃, and Li₂S-P₂S₅-Z. m S n (m and n are positive numbers, Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (p and q are positive numbers, M is P, Si, Ge, B, Al, Ga, or In), Li7-xPS6-xCl x (0≤x≤2), Li7-xPS6-xBr x (0≤x≤2), Li7-xPS6-xI x (0≤x≤2), etc. These can be used individually or in combination of two or more.

[0115] In one embodiment, the solid electrolyte may further include oxide-based amorphous solid electrolytes such as Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3, and Li2O-B2O3-ZnO.

[0116] like Figure 1 As shown, the tabs (positive tab and negative tab) can protrude from the positive current collector 105 and negative current collector 125 belonging to each cell and extend to one end of the housing 160. The tabs can be fused to said end of the housing 160 and connected to electrode leads (positive lead 107 and negative lead 127) extending to or exposed outside the housing 160.

[0117] Although Figure 1 The diagram shows the positive electrode lead 107 and the negative electrode lead 127 protruding from the upper edge of the housing 160 in the planar direction, but the position of the electrode leads is not limited thereto. For example, the electrode leads may also protrude from at least one of the two sides of the housing 160, or from the lower edge of the housing 160. Alternatively, the positive electrode lead 107 and the negative electrode lead 127 may be formed to protrude from different edges of the housing 160, respectively.

[0118] The lithium secondary battery can be manufactured in shapes such as cylindrical, prismatic, pouch, or coin, for example, using a can.

[0119] The following preferred embodiments are presented to help understand the present invention. However, these embodiments are only for illustrating the present invention and are not intended to limit the scope of the claims. Various changes and modifications can be made to the embodiments within the scope of the present invention and the technical concept. This is obvious to those skilled in the art, and it is natural that such variations and modifications fall within the scope of the claims.

[0120] Examples and Comparative Examples (1) Preparation of positive electrode active material Example 1 1) Preparation of large particles NiSO4, CoSO4, and MnSO4 were mixed in a molar ratio of 87:9:4 using distilled water that had been bubbled with N2 for 24 hours to remove dissolved oxygen. The solution was then added to a reactor at 50°C, where a co-precipitation reaction was carried out for 48 hours using NaOH and NH3·H2O as precipitating and chelating agents, respectively, to form nickel-cobalt-manganese hydroxide (a composite metal salt compound) with a particle size of approximately 8.0 μm to 13.0 μm. During this process, the concentration and amount of NaOH and NH3·H2O were adjusted to control the pH to ensure uniform crystal growth. The composite metal salt compound was dried at 80°C for 12 hours and then further dried at 110°C for 12 hours.

[0121] Next, lithium hydroxide was added to achieve a ratio of 1:1.05 between the composite metal salt compound and lithium hydroxide, and then the mixture was stirred and mixed uniformly for 5 minutes. The mixture was then placed in a calcination furnace and heated to 710°C at a rate of 2°C / min, and maintained at 710°C for 10 hours. During the heating and holding period, oxygen was continuously introduced at a flow rate of 10 mL / min. After calcination, the mixture was allowed to cool naturally to room temperature and then pulverized and graded. At this point, zirconia balls were used for pulverization via a ball mill, adjusting the ball size and milling time to obtain large particles.

[0122] 2) Preparation of small particles The same process as that used for preparing the large particles was performed to obtain small particles with a particle size of approximately greater than 1.0 μm and less than 6.0 μm. The difference was that, in the preparation of nickel cobalt manganese hydroxide, the concentrations and amounts of NaOH and NH3·H2O were adjusted to control the pH.

[0123] Examples 2 to 9 Large and small particles were prepared using the same method as in Example 1, except that the co-precipitation time was changed to 45 hours, and the concentrations and amounts of NaOH and NH3·H2O were adjusted separately to meet the conditions in Table 1.

[0124] Comparative Examples 1 to 8 Large and small particles were prepared using the same method as in Example 1, except that the co-precipitation time was changed to 40 hours, and the concentrations and amounts of NaOH and NH3·H2O were adjusted separately to meet the conditions in Table 1.

[0125] 3) Roundness measurement The roundness of the positive electrode active materials prepared in the examples and comparative examples was measured using a particle morphology analyzer (Morphologi 4, Malvern Corporation). Specifically, 1 mm particles were measured... 3 The positive electrode active material samples of the examples and comparative examples prepared described above were dispersed under conditions of 4 bar and 10 milliseconds (ms), and then the large and small particles of the examples and comparative examples were analyzed by two-dimensional images.

[0126] Subsequently, the roundness of the 10,000 large particles and / or small particles of the embodiments and comparative examples was measured.

[0127] The average (C) of the roundness of the large particles according to the embodiments and comparative examples will be used to determine the sphericity. L ), the average roundness of small particles (C S ) and the average roundness of the large particles (C L The ratio of (C) S / C L The results of calculations on the relative standard deviation of the roundness of large particles are shown in Table 1 below.

[0128] [Table 1] (2) Manufacturing of secondary batteries Secondary batteries were manufactured using the positive electrode active materials of the examples and comparative examples described in Table 1. Specifically, the positive electrode active material, acetylene black (Denka Black) as a conductive material, and PVDF as a binder were mixed in a mass ratio of 98:1:1 to prepare a positive electrode mixture, which was then coated onto an aluminum current collector and dried, and then rolled at a pressure of 20 MPa to manufacture the positive electrode.

[0129] A negative electrode slurry is prepared, comprising 94 wt% natural graphite as the negative electrode active material, 3 wt% flake-type conductive material KS6 as the conductive material, and 3 wt% styrene-butadiene rubber (SBR) as the binder. The negative electrode slurry is coated onto a copper substrate and then dried and pressed to manufacture the negative electrode.

[0130] The positive and negative electrodes manufactured as described above are cut (notched) to specified dimensions and stacked. A separator (polyethylene, 25 μm thick) is placed between the positive and negative electrodes to form a battery cell. Then, the tab portions of the positive and negative electrodes are welded together. The welded positive / separator / negative electrode assembly is placed in a soft package, and the three sides except for the electrolyte injection side are sealed. At this time, the portion with the electrode tabs is included in the sealed portion. Electrolyte is injected through the remaining sides except for the sealed portion, and the remaining sides are sealed, and then immersed for at least 12 hours.

[0131] The electrolyte was prepared by dissolving 1M LiPF6 in a mixed solvent of EC / EMC / DEC (25 / 45 / 30; volume ratio), and then adding 1% by weight of fluoroethylene carbonate (FEC), 0.3% by weight of 1,3-propenyl sulpholol (PRS), 0.5% by weight of propane sulpholol (PS), and 0.5% by weight of vinyl sulfate (ESA).

[0132] Experimental Example (1) Initial discharge capacity (mAh / g) The manufactured lithium secondary battery was charged in a chamber at 25°C (CC / CV, rate of 0.1C, upper limit voltage of 4.3V, 0.05C cut-off), and then the battery capacity (initial charge capacity) was measured. After discharging again (CC 0.1C 3.0V cut-off), the battery capacity (initial discharge capacity) was measured.

[0133] (2) Capacity retention rate at 25℃ (%) For the manufactured secondary battery, at 25°C, charging (CC / CV, 1.0C, 4.3V, 0.05C cutoff) and discharging (CC, 1.0C, 3.0V cutoff) are considered as one cycle, and the discharge capacity after one cycle is measured.

[0134] The cycle was repeated 500 times, and the cycle capacity retention rate at 25°C was evaluated as a percentage of the discharge capacity at the 500th cycle divided by the discharge capacity at the 1st cycle.

[0135] (3) Capacity retention rate at 45℃ (%) For the manufactured secondary battery, at 45°C, charging (CC / CV, 1.0C, 4.3V, 0.05C cutoff) and discharging (CC, 1.0C, 3.0V cutoff) are considered as one cycle, and the discharge capacity after one cycle is measured.

[0136] The cycle was repeated 500 times, and the cycle capacity retention rate at 45°C was evaluated as a percentage of the discharge capacity at the 500th cycle divided by the discharge capacity at the 1st cycle.

[0137] (4) Gas production at 45℃ (mL) For the manufactured secondary batteries, charging (CC / CV, 1.0C, 4.3V, 0.05C cutoff) and discharging (CC, 1.0C, 3.0V cutoff) were performed at 45°C as one cycle, and this cycle was repeated 500 times. After that, the batteries were left at room temperature for 1 hour, and then placed in a chamber for measuring the amount of gas generated.

[0138] The chamber is evacuated and then filled with nitrogen to atmospheric pressure. The nitrogen volume (V0) and the internal pressure (P0) are then measured. The chamber is evacuated again, and an opening is made in the battery to measure the internal pressure (P1). The amount of gas produced by the battery is measured using Equation 2 below.

[0139] [Equation 2] Gas production (mL) = V0 / P0×P1 The evaluation results are recorded in Table 2 below.

[0140] [Table 2] Referring to Tables 1 and 2, the average (C) of large particles that simultaneously satisfy a sphericity greater than 0.95 and less than 1 is... L The average roundness of small particles (C) is 0.90 to 0.99. S ) and the average roundness of large particles (C L The ratio of (C) S / C L In the embodiments with a relative standard deviation of 1 to 5 for the roundness of large particles, the overall capacity retention is high and the amount of gas generated is low.

[0141] On the other hand, compared with the embodiments, in the comparative examples where one or more items did not meet the above range, the overall capacity retention rate was lower and the gas production was higher.

Claims

1. A positive electrode active material for lithium secondary batteries, comprising: Large particles; and Small particles, the average particle size D of which is... 50 Smaller than the aforementioned large particles, in, The average roundness of the large particles is greater than 0.95 and less than 1. The average C of the roundness of small particles S The average C of the roundness of the large particles L The ratio of C S / C L The value ranges from 0.90 to 0.

99. The relative standard deviation of the roundness of the large particles is 1 to 5. The roundness is defined by the following equation 1: [Formula 1] Roundness = 4π × (A / P) 2 ) In Equation 1, A is the area of ​​the particle cross-section, and P is the perimeter of the particle cross-section.

2. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The large particles and the small particles comprise lithium nickel metal oxide particles.

3. The positive electrode active material for lithium secondary batteries according to claim 2, wherein, The lithium-nickel metal oxide particles are represented by the following chemical formula 1: [Chemical Formula 1] Li x Ni a M b O 2+z In the chemical formula 1, M is at least one element selected from B, Al, Si, Ti, V, Cr, Mg, Mn, Fe, Co, Cu, Zn, Y, Nb, Zr, Mo, Sn, Sr and W, with 0.9≤x≤1.2, 0.6≤a≤0.99, 0.01≤b≤0.4, and -0.5≤z≤0.

1.

4. The positive electrode active material for lithium secondary batteries according to claim 3, wherein, In the chemical formula 1, 0.8 ≤ a ≤ 0.

95.

5. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The average particle size D of the large particles 50 Greater than 10.0 μm and less than 15.0 μm.

6. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The average particle size D of the small particles 50 Greater than 1.0 μm and less than 8.0 μm.

7. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The average C of the roundness of the large particles L It is greater than 0.97 and less than 1.

8. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The average C of the roundness of the large particles L It is greater than 0.99 and less than 1.

9. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The average C of the roundness of the small particles S The average C of the roundness of the large particles L The ratio of C S / C L The value ranges from 0.92 to 0.

97.

10. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The average C of the roundness of the small particles S The average C of the roundness of the large particles L The ratio of C S / C L It ranges from 0.93 to 0.

96.

11. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The relative standard deviation of the roundness of the large particles is 1 to 4.

12. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The relative standard deviation of the roundness of the large particles is 1 to 3.

13. The positive electrode active material for lithium secondary batteries according to claim 1, wherein, The mixing weight ratio of the large particles to the small particles is 6:4 to 9:

1.

14. A positive electrode for a lithium secondary battery, comprising: Positive current collector; as well as A positive electrode active material layer, the positive electrode active material layer comprising the positive electrode active material for lithium secondary batteries as described in claim 1, formed on the positive electrode current collector.

15. A lithium secondary battery, comprising: The positive electrode for a lithium secondary battery as described in claim 14; The negative electrode is positioned opposite to the positive electrode. as well as A diaphragm is disposed between the positive electrode and the negative electrode.